2020
DOI: 10.3390/foods9121813
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Changes during the Manufacture of Galician Chorizo Sausage as Affected by the Addition of Autochthonous Starter Cultures

Abstract: In this work, the effect of the use of two autochthonous starter cultures (Lactobacillus sakei LS131 + Staphylococcus equorum SA25 (EQU), or L. sakei LS131 + Staphylococcus saprophyticus SB12 (SAP)) on the physicochemical, microbiological, proteolytic and lipolytic changes taking place during the manufacture of Galician chorizo, a traditional Spanish sausage, was studied. Three different batches (control (CNT), EQU and SAP) were manufactured in triplicate and analysed during the manufacturing process (samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 83 publications
3
15
0
Order By: Relevance
“…2. The initial pH at day 0 in DFS without starter culture added and without HPP (A-INP), was 6.0 ± 0.1, which is in agreement with results from previous studies with south European DFS (Juárez-Castelán et al, 2019;Martín et al, 2021;Rodríguez-González, Fonseca, Centeno, & Carballo, 2020). The pH drop was more pronounced initially in sausages with starter (p < 0.05), similar to what Latorre-Moratalla et al ( 2007) found.…”
Section: Evolution Of Physicochemical Parameterssupporting
confidence: 91%
“…2. The initial pH at day 0 in DFS without starter culture added and without HPP (A-INP), was 6.0 ± 0.1, which is in agreement with results from previous studies with south European DFS (Juárez-Castelán et al, 2019;Martín et al, 2021;Rodríguez-González, Fonseca, Centeno, & Carballo, 2020). The pH drop was more pronounced initially in sausages with starter (p < 0.05), similar to what Latorre-Moratalla et al ( 2007) found.…”
Section: Evolution Of Physicochemical Parameterssupporting
confidence: 91%
“…In fact, chorizo samples showed a very low pH (between 4.52 and 5.04), while the salchichón had a pH ranging from 5.13 to 5.83. There are different set of data reported in the literature for chorizo characteristics, and among them the pH can vary: results of Galician chorizo showed a pH value of about 5.6 [24], while Asturian products had pH between 5.0 and 5.1 [25].…”
Section: Physico-chemical Characterizationmentioning
confidence: 99%
“…In local varieties of fermented sausages having a strong personality and with defined and loyal markets, the use of autochthonous starter cultures is the most appropriate way to obtain manufactured products that are uniform, of high and constant quality and that retain the differentiated attributes of their homonyms artisanally obtained through spontaneous fermentations. Rodríguez-González et al [ 13 ] studied the effect of the addition of two different autochthonous starter cultures including one strain of Lactobacillus sakei and one of Staphylococcus equorum or Staphylococcus saprophyticus on the biochemical changes occurring during the manufacture of Galician chorizo sausage, the most popular traditional meat product in the NW Spain. Along the manufacture of three independent batches made with each of the two starter cultures, they studied the changes in proximate composition, pH, Aw, color parameters, nitrogen fractions, free amino acids, biogenic amines, fat parameters, and free fatty acids.…”
mentioning
confidence: 99%